Biosynthesis of D-Mannitol by Diplodia pinea (Research, Society and Development, 2021)
Research with fungi in search of substances with potential biological activity is gaining more prominence since they are sustainable sources of new molecules. Diplodia pinea is a phytopathogenic fungus found in forest species, which has shown few reports of molecules with biological activity and may present promising biotechnological potential. Thus, the objective of this study was to detect substances produced by this fungus in a liquid medium, under stressful conditions. A metabolite was detected in the alcoholic fraction characterized by X-ray diffraction as D-mannitol. This is the first description of this monosaccharide produced by D. pinea.